A microfluidic platform for anterior-posterior human endoderm patterning via countervailing morphogen gradients in vitro - Leeya Engel; Kevin J. Liu; Kiara W. Cui; Eva L. de la Serna; Vipul T. Vachharajani; Carolyn E. Dundes; Sherry Li Zheng; Manali Begur; Kyle M. Loh; Lay Teng Ang; Alexander R. Dunn (iScience)
Summary: Understanding how morphogen gradients spatially pattern tissues is a fundamental question in developmental biology but can be difficult to directly address using conventional approaches. Here, we expose hPSC-derived endoderm cells to countervailing gradients of anteriorizing and posteriorizing signals using a widely available microfluidic device. This approach yielded spatially patterned cultures comprising anterior foregut (precursor to the thyroid, esophagus, and lungs) and mid/hindgut (precursor to the intestines) cells, whose identities were confirmed using single-cell RNA sequencing (scRNA-seq). By exposing stem cells to externally applied signaling gradients, this widely accessible microfluidic platform should accelerate the production of spatially patterned tissues, complementing internally self-organizing organoids. Applying artificial morphogen gradients in vitro may also illuminate how developing tissues interpret signaling gradients in systems that are not readily accessible for in vivo studies.